2020
DOI: 10.1002/pits.22434
|View full text |Cite
|
Sign up to set email alerts
|

Personality traits and job exploration among Latino business students: An exploratory investigation

Abstract: We examine the role of the Big Five personality traits in the job exploration process of Latino undergraduate business students to ascertain the personality traits and socio-cognitive variables that lead to greater success of students in their job searches. We find that personalities such as extraversion and conscientiousness are positively associated with career selfefficacy, career expectations, and interests in both academic and professional skills, which in turn positively influence job exploration behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 49 publications
1
9
1
Order By: Relevance
“…On the one hand, individuals high in conscientiousness are likely to be more effective at regulating negative affect [ 18 ] and may experience less daily stress [ 27 , 32 ]. On the other hand, individuals high in conscientiousness are more likely to be self-disciplined, goal-directed, industrious, and rule-abiding [ 4 ], and their efficient and reliable performance may promote success in school or the workplace [ 5 , 6 , 8 , 9 ]. Such success can help to enhance their subjective well-being [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, individuals high in conscientiousness are likely to be more effective at regulating negative affect [ 18 ] and may experience less daily stress [ 27 , 32 ]. On the other hand, individuals high in conscientiousness are more likely to be self-disciplined, goal-directed, industrious, and rule-abiding [ 4 ], and their efficient and reliable performance may promote success in school or the workplace [ 5 , 6 , 8 , 9 ]. Such success can help to enhance their subjective well-being [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Over the past few decades, a great number of studies have linked personality traits with well-being [ 1 , 2 , 3 ]. Among the Big Five personality traits, conscientiousness reflects a set of characteristics describing industriousness, orderliness, goal-directed, planning, impulse control, delayed gratification, active coping, and the propensity to adhere to societal rules and norms [ 4 ], which is related to a serial of social adaptive outcomes, such as better work performance [ 5 ], higher career self-efficacy [ 6 ], positive interpersonal relationships [ 7 ] and higher academic effort [ 8 ] or achievement [ 9 ]. Notably, conscientiousness was found to be closely linked with an individual’s mental and physical health [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research suggests that career and occupational choice reflects inner working structural components reflecting person-level variables, including temperament, personality, and dispositional traits (He et al, 2021;Ripski et al, 2011;Sui et al, 2021;Yusof et al, 2020). This study, therefore, includes a separate investigation exploring attachment dimensions relative to employee selection of the job sector, as different sectors of employment, have different expectations for workers (Furnham & Fudge, 2008;van Dolen et al, 2002).…”
Section: Current Study and Rationalementioning
confidence: 97%
“…For example, Yang and Hwang [61] analyzed the relationship between personality traits and job performance in Chinese employee management, and found that the Big Five personality traits significantly affect job performance, of which agreeableness has the largest impact, followed by extraversion. Similarly, Sui et al [62] analyzed the relationship between the Big Five personality traits and career exploration behavior, and found that extroversion and conscientiousness positively correlated with career expectations, and had a positive impact on job exploration behavior. Therefore, consistent with previous studies, this research concluded that miners' work commitment was significantly different due to individual personality characteristics.…”
Section: Work Commitment and Individual Personality Characteristicsmentioning
confidence: 99%